PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL MENENGAH BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (Studi Pada Waserda Di Kecamatan Tenayan Raya, Pekanbaru) - Indah Harnum; Makhdalena Makhdalena; R.M. Riadi R.M. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The focus of the problem in this research is: to know the suitability of accounting application of Micro, Small and Medium Enterprises (SMEs) in Lintas Timur Street Tenayan Raya District, Pekanbaru with generally accepted accounting principles. The financial statements discussed in this study are limited to the Income Statement, with a total population of 38 SMEs. Method of data analysis using descriptive qualitative. Based on the results of research minimarket in District Tenayan Raya Pekanbaru City has not applied the accounting of Micro Small and Medium Enterprises in accordance with generally accepted accounting principles in the recording and preparation of balance sheet and income statement. This can be seen from the responses of respondents where most of which is 27 or 70.05% minimarket does not record in the journal accounting and as much as 28 or 75% minimarket declare are not to separate between business finance and household finances, then about the presentation of income statement, 24 or 63.16% of minimarket states does not make income statement with reason that they do not understand how to make financial statement. All minimarket in Lintas Timur Street Tenayan Raya Sub-district Pekanbaru City has made general journal book, but there are only 8 or 21,05% minimarket which make daily journal, cash receipt book and book of cash expenditure. As for the other records, none of the minimarket made it.Keyword: Small and Medium Enterprises and Financial report